Germline CDKN2A/P16INK4A mutations contribute to genetic determinism of sarcoma. Issue 9 (7th June 2017) - Jouenne, Fanélie; Chauvot de Beauchene, Isaure; Bollaert, Emeline; Avril, Marie-Françoise; Caron, Olivier; Ingster, Olivier; Lecesne, Axel; Benusiglio, Patrick; Terrier, Philippe; Caumette, Vincent; Pissaloux, Daniel; de la Fouchardière, Arnaud; et al.
Abstract : Background: Sarcomas are rare mesenchymal malignancies whose pathogenesis is poorly understood; both environmental and genetic risk factors could contribute to their aetiology. Methods and results: We performed whole-exome sequencing (WES) in a familial aggregation of three individuals affected with soft-tissue sarcoma (STS) without TP53 mutation (Li-Fraumeni-like, LFL) and found a shared pathogenic mutation in CDKN2A tumour suppressor gene. We searched for individuals with sarcoma among 474 melanoma-prone families with a CDKN2A -/+ genotype and for CDKN2A mutations in 190 TP53 -negative LFL families where the index case was a sarcoma. Including the initial family, eight independent sarcoma cases carried a germline mutation in the CDKN2A /p16 INK4A gene. In five out of seven formalin-fixed paraffin-embedded sarcomas, heterozygosity was lost at germline CDKN2A mutations sites demonstrating complete loss of function. As sarcomas are rare in CDKN2A /p16 INK4A carriers, we searched in constitutional WES of nine carriers for potential modifying rare variants and identified three in platelet-derived growth factor receptor ( PDGFRA ) gene. Molecular modelling showed that two never-described variants could impact the PDGFRA extracellular domain structure. Conclusion: Germline mutations in CDKN2A /P16 INK4A, a gene known to predispose to hereditary melanoma, pancreatic cancer and tobacco-related cancers, account also for a subset of hereditary sarcoma. In addition, we identified PDGFRA as a candidate modifier gene.